Towards a Posthuman Sexuality: Art, Sex and Evolution in Nietzsche, Williams and Mozart - Steinbuch, Thomas A. (Journal of Posthumanism, 2022)
My paper is a study of art, sex and evolution as they are entwined in the text of On Those Who Are Sublime from Nietzsche’s Thus Spoke Zarathustra and other related texts from that work. N. introduces the thought of the Dionysian orgy in connection with the work of art, which should be Dionysian art, and in this meaning, the sexual orgy signifies evolution. My paper further attempts to identify art, sex and evolution in the context of evolution out of the mind of domination arguing that here evolution means experiencing freedom and backtracking from rape sex to anonymity in sex. A close reading is made of the psychology of domination in Tennessee Williams’ drama A Streetcar Named Desire I present a new interpretation of Mozart’s Don Giovanni as a search, however unclearly, for a post human sexuality. I draw on the works of Wilhelm Reich’s classics of the literature of the Frankfurt School on the critique of authoritarianism, and interrogate the idea of truthfulness promoted on the far right.